2007
DOI: 10.1016/j.jfca.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of South African fortification legislation on product formulation for low-income households

Abstract: Newly introduced legislation for the fortification of maize meal and bread flour in South Africa enhanced nutritive intakes for selected nutrients and enabled the formulation of an affordable, dry, plant-based premixed food product for low-income households. Firstly, the nutritive intakes and relatedness to prevalent nutrient deficiencies in South Africa were calculated to portray the impact of the implemented food fortification legislation were indicated as limitations and relaxed to derive a reasonable answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This 200 g raw weight translates into approximately 370 g baked brown bread and depending upon the consistency of cooked maize porridge, between 530 g (stiff porridge) and 1450 g (soft porridge) that should be consumed to meet the RDAs. As stated previously, the 2005 study by Duvenhage and Schönfeldt (2007) reported the average daily intake of maize porridge to be 532 g. This is in line with the amounts required for stiff maize porridge, while daily bread intakes were reported to be much lower than the required amounts at approximately 150 g/day. Bearing in mind that the effect of inflation may result in consumers employing coping strategies such as consuming even smaller food portions, it is possible that current daily intakes may be even less than those recorded in 2005.…”
Section: South African Approach To Combat Malnutritionsupporting
confidence: 71%
See 1 more Smart Citation
“…This 200 g raw weight translates into approximately 370 g baked brown bread and depending upon the consistency of cooked maize porridge, between 530 g (stiff porridge) and 1450 g (soft porridge) that should be consumed to meet the RDAs. As stated previously, the 2005 study by Duvenhage and Schönfeldt (2007) reported the average daily intake of maize porridge to be 532 g. This is in line with the amounts required for stiff maize porridge, while daily bread intakes were reported to be much lower than the required amounts at approximately 150 g/day. Bearing in mind that the effect of inflation may result in consumers employing coping strategies such as consuming even smaller food portions, it is possible that current daily intakes may be even less than those recorded in 2005.…”
Section: South African Approach To Combat Malnutritionsupporting
confidence: 71%
“…Maize porridge consumption by this population in 2006 amounted to approximately 532 g/day (made up according to meal times as 345 g stiff maize porridge plus 124 g soft maize porridge plus 63 g crumbly maize porridge), eaten over two or three meals, and representing 66% of their total energy intake per day (Oldewage‐Theron et al . 2006; Duvenhage & Schönfeldt 2007). These portion sizes are significantly lower than those reported in the South African food consumption studies carried out among different population groups between 1983 and 2002 (Nel & Steyn 2002) (as illustrated in Table 1).…”
Section: South African Consumer Food Purchasing Behaviourmentioning
confidence: 99%
“…Unfortunately, white maize is high in starch and limited in micronutrients [ 25 ]. As a result, complementary foods made with white maize as the main or sole solid ingredient, such as soft maize porridge is generally adequate in energy, fibre, and B-vitamins, but deficient in protein and minerals such as iron, calcium, and zinc [ 27 , 28 ]. Although mothers in the current study indicated that other ingredients such as sugar, milk powder, margarine, or peanut butter were added to white maize soft porridge, the porridge may still be nutritional-deficient, as the nutrients may be reduced by overcooking and overdilution of ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…This association between income and anemia is also evident in high‐income countries, where people of low socioeconomic status are especially susceptible to deficiencies in iron and other vitamins and minerals . Low‐income families are more likely to base their diet on staple foods . Therefore, access to fortified maize flour and corn meal seems to be mediated by their costs.…”
Section: Equity In Access To Fortified Maize Flour and Corn Mealmentioning
confidence: 99%